2013
DOI: 10.1590/s1517-83822013005000005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of kefir yeast potential for sugar/ethanol-resistance

Abstract: Biochemical and molecular analysis was used for identification of different kefir yeasts species from Brazil, Canada and the United States of America. The sugar/ethanol-resistant activity of the yeasts was evaluated. Saccharomyces cerevisiae and Kluyveromyces marxianus had the highest growth rates, suggesting biotechnological applications possible for these strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
3
9
1
1
Order By: Relevance
“…Compared to Hmp-1, S. cerevisiae FM-S-115 showed stronger resistance to ethanol, and could still grow at a concentration of 14% (v/v) ethanol. This result was in agreement with previous reports (Fugelsang and Edwards 2007;Miguel et al 2013;Contreras et al 2014).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Compared to Hmp-1, S. cerevisiae FM-S-115 showed stronger resistance to ethanol, and could still grow at a concentration of 14% (v/v) ethanol. This result was in agreement with previous reports (Fugelsang and Edwards 2007;Miguel et al 2013;Contreras et al 2014).…”
Section: Discussionsupporting
confidence: 94%
“…It had been reported that ethanol could damage mitochondrial DNA of yeast cells and lead to inactivation of some enzymes, such as hexokinase and dehydrogenase (Ibeas and Jimenez 1997). A previous study found that P. membranifaciens could not grow at a concentration of 6% (v/v) ethanol (Miguel et al 2013). In this study, P. membranifaciens strain Hmp-1 could still grow and form pellicle in the blackberry wine containing 8.05% (v/v) ethanol.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, S. cerevisiae was present in all three sugary kefir grains as the predominant yeast, while K. marxianus formed a secondary microbiota in two out of three sugary kefir grains, namely BSS and NAJ kefir grains. Regarding S. cerevisiae, these findings are in agreement with previous studies [3,5,6,16], which confirmed the high prevalence of this yeast species in sugary kefir grains. On the other hand, although K. marxianus presence in sugary kefir grains has been previously reported [16], this yeast is isolated from milk kefir grains more frequently as part of the secondary microbiota [17].…”
Section: Discussionsupporting
confidence: 92%
“…e Zygosaccharomyces sp. foram reportadas em outras pesquisas com grãos de Kefir obtidos em outros países como Canadá e Estados Unidos da América (MIGUEL et al, 2012;AHMED et al, 2015), o que remete ao fato de que grãos obtidos em diferentes regiões podem apresentar constituições distintas em relação a população microbiana encontrada na matriz de polissacarídeos (LEITE et al, 2013) e ainda a necessidade de continuidade do presente estudo com o intuito de identificar biomolecularmente as leveduras isoladas.…”
Section: Discussionunclassified